Type 1 Diabetes in 2023 From Real Practice to Open Questions - Chlup, Rudolf (IntechOpen, 2023)
Type 1 diabetes is a complex and challenging health condition that affects up to 2% percent of the global population. This book provides a comprehensive overview of this chronic clinical entity, focusing on causes, development, and management. It includes nine chapters that address such topics as managing diabetes using insulin and medical devices such as pens and pumps, how lifestyle affects diabetes, biomarkers for the disease, and much more.